Development of The Insightful EducatorHub Platform to Enhance Technology-Based Mentoring Collaboration in The Teacher Professional Education Program - Ibrohim, Ibrohim; Muksar, Makbul; Yulianti, Erni; Sumberartha, I Wayan; Hajar, Maya Umi (Universitas Sebelas Maret, 2024)
Traditional mentoring within teacher education often struggles with inconsistent interaction, vague feedback, and inefficient communication, which collectively hinder the professional growth of teacher candidates. The Insightful EducatorHub platform was developed to address these issues by leveraging a digital solution with real-time communication tools, structured feedback mechanisms, and collaborative spaces. This study aimed to improve mentoring collaboration through a research and development (R&D) approach using the ADDIE model. The platform was tested with 30 teacher candidates, five mentor teachers, and five supervisors from five schools. Data were collected through pre- and post-implementation surveys and semi-structured interviews. Quantitative findings indicated a 35% increase in interaction frequency and a 40% improvement in participant satisfaction levels. At the same time, mentors and supervisors recognized the platform’s utility in organizing tasks and consolidating mentoring processes. Although prosperous, the trial identified areas for refinement, including greater customization and advanced analytics to better suit diverse educational settings while demonstrating Insightful EducatorHub’s promise as an innovative tool for elevating mentoring practices and supporting the professional development of future educators.